The reasonable robot – introduction: Artificial Intelligence and the law - Abbott, Ryan (Revista Rede de Direito Digital, Intelectual & Sociedade, 2023)
Artificial intelligence (AI) and people do not compete on a level playing field. Self-driving vehicles may be safer than human drivers, but laws often penalize such technology. People can provide superior customer service, but companies are automating to reduce their taxes. AI can innovate more effectively, but an antiquated legal framework restricts inventive AI. In The Reasonable Robot, Ryan Abbott argues that the law should not discriminate between AI and human behavior and proposes a new legal principle that will ultimately improve human welfare. This work should be read by anyone interested in the rapidly evolving relationship between AI and the law.